Effect of the use of a model with peer instruction for the teaching of membrane potential and action potential - Albuquerque, Fabíola da Silva; Assis, Temilce Simões de; Oliveira Júnior, Francisco Antônio de; Freitas, Maria Regina de; Sá, Rita de Cássia da Silveira e; Martins, Vinícius José Baccin; Lins, Larissa Suelen da Silva; Araújo, Juliany Santiago de; Sousa, Nattan Almeida e; Gouveia, Rachel Linka Beniz (Advances in physiology education, 2018)
A group of teachers from Northeast Brazil developed a model of membrane potentials and action potential and tested the hypothesis that using the peer-instruction model would provide a better performance for students in reading traditional texts and lectures. The results were obtained from 357 students from 20 different courses in 9 different undergraduate programs. All students attended two 100-min theoretical lecture and, at the end of the second lecture, were asked to answer a multiple-choice question (a pretest). In the following lecture, students were divided into three groups: control, text, and model. At the end of the lecture, everyone responded to a posttest. Student performance in the pretest did not differ significantly between groups. In the comparison between the pretest and the posttest, students in the model and text groups significantly improved their performance, but there was no improvement in the control group. In the posttest, the model group presented a better performance than the control group. In the evaluation of the strategies used, 46% of the students indicated that the text would be very useful to remind them about the subject in the future, whereas 80% of those who used the model indicated that it would be very useful or extremely useful. useful. Although it was not possible to support the hypothesis conclusively, the performance model group, at least in part, was due to the use of active methodologies that constitute a differential in the teaching-learning process.